2016
DOI: 10.1016/j.athoracsur.2016.02.107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radial Artery and Saphenous Vein Graft Stenosis More Than 5 Years After Coronary Artery Bypass Grafting

Abstract: There was no significant difference in the rates of significant stenosis of patent RA grafts and SVGs more than 5 years postoperatively. However, the burden of graft body stenosis was less in RA grafts compared with SVGs, suggesting that the RA grafts will continue to outperform the SVGs late after operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Patients in both groups did not develop myocardial infarction (MI), angina, ECG changes and echocardiographic changes after surgery and during the follow up period these good results was mostly because those patients were selected with good targets, good ejection fraction, and no comorbidities to avoid any factor that may affect the durability of the conduits. So, short term follow up showed no ischemic cardiac complications when both conduits (SVG and radial artery) were used, and these results are similar to the results of the study of Yamasaki et al in 2016 [8].…”
Section: Comparative Study Between the Use Of The Radial Artery And Tsupporting
confidence: 88%
“…Patients in both groups did not develop myocardial infarction (MI), angina, ECG changes and echocardiographic changes after surgery and during the follow up period these good results was mostly because those patients were selected with good targets, good ejection fraction, and no comorbidities to avoid any factor that may affect the durability of the conduits. So, short term follow up showed no ischemic cardiac complications when both conduits (SVG and radial artery) were used, and these results are similar to the results of the study of Yamasaki et al in 2016 [8].…”
Section: Comparative Study Between the Use Of The Radial Artery And Tsupporting
confidence: 88%
“…41 In an analysis of the RAPS trial examining late angiographic follow-up, Yamasaki and co-authors found that the incidence of adverse clinical events and need for revascularization was significantly higher in patients with graft stenosis (p<0.0001 and p<0.0009, respectively). 47 The lack of a constant correlation between graft failure and clinical event is likely related to the different amount of myocardium supplied by the failed graft.…”
Section: Clinical Consequences Of Graft Failurementioning
confidence: 99%
“…Similar patency rates at 1 year were also observed among 11 Veterans affairs centers enrolling patients for radial versus SVG during CABG. 40) The Canadian multicenter Radial Artery Patency Study (RAPS), 41) which enrolled 163 patients for radial versus SVG grafting, did not show differences of the rates of ≥50% stenosis in the radial grafts and SVG at 5-year. However, the burden of graft stenosis was significantly higher in the SVG arm compared to radial graft arm suggesting potential better long-term patency with radial grafts.…”
Section: Multivessel Cadmentioning
confidence: 99%